The Evolution of Dedicated Satellite Missions: Innovations, Obstacles, and Future Potential - Mishra, Meghana (Journal of Advanced Research in Geo Sciences & Remote Sensing; Vol 11 No 3&4 (2024): Journal of Advanced Research in Geo Sciences & Remote Sensing, 2024)
Dedicated satellite missions have become an essential component of modern space explorati on and technology, offering specialized soluti ons for a wide array of applicati ons ranging from Earth observati on and telecommunicati ons to scientific research and nati onal security. These missions, which focus on a singular objective or a set of closely related goals, have evolved dramatically due to advancements in satellite miniaturization, propulsion technology, data processing, and communicati on systems. While these innovations have expanded the capabilities of satellites, challenges related to cost, space debris, technological reliability, and regulatory frameworks remain significant barriers. As the demand for space-based services continues to grow, the future of dedicated satellite missions promises new opportunities, including interplanetary exploration, global satellite constellati ons, arti fi cial intelligence-driven autonomy, and sustainable space operati ons. This review explores the evolution of dedicated satellite missions, highlights the technological advancements that have reshaped the field, examines the challenges that must be overcome, and discusses the promising future directions for these missions in anincreasingly commercialized and interconnected space environment.